(3GdeSFhdjI GdLfGFjI Yf LQjeI GdGMJLGR ZjQ GdeTQhY (B/ s - (3YeQGdNWGH TMGJI eMeO SjOs; (3YeQ eMeO SGde s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2013)
(3JOhQ GdQSGdI Mhd (B"(3GdeSFhdjI GdLfGFjI Yf LQjeI GdGMJLGR ZjQ GdeTQhY(B" (3h (B((3LQjeI GdGMJLGR ZjQ GdeTQhY(B) (3gj EMOi Cge LQGFe GdGYJOGA Ydi GdMQjI GdTNUjI(B: (3h Je GdMOjK Yf GdeSFhdjI GdLfGFjI Yf gPg GdLQjeI ef NdGd GdJYQV deGgjI GdMQjGJ GdTNUjI h JYQjagG(B: (3h TQM GdQcfjf GdeGOj h GdeYfhj dgPg GdLQjeI(B: (3h cPG GdJYQV dPGJjI gPg GdLQjeI h eG jejRgG Yf ZjQgG ef GdELQGAGJ h GdLQGFe GdJj bO JJTGHg Ch JJOGNd eYgG(B: (3h CNjQG GdYbhHGJ GdJj bQQgG GdeTQY dgPg GdLQjeI h bO JHjf YOe caGjJgG dJMbjb GdQOYjf GdYGe h GdNGU s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb, (B2013(3, bSe GdbGfhf GdLfGFjs
(3HHdjhLQGajG(B: (3UaMGJ (B334-364s
Keywords: (3GdMQjGJ GdaQOjIs; (3GdGSJjbGas; (3LQjeI GSJYeGd GdbShIs; (3GQcGf LQjeI GdCMJLGR ZjQ GdeTQhYs; (3LQjeI GdNWas; (3GdbUO GdLfGFjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs